Anaerobic Digestion of Wastewater with High Sulfate Concentration Using Micro-Aeration and Natural Zeolites - Perez-Jara, P; Huilinir-Curio, C; Montalvo-Martinez, S (Assoc. Brasiliera de Eng. Quimica / Braz. Soc. Chem. Eng., 2016)
The behavior of anaerobic digestion in batch and UASB reactors using a microaerobic process and natural zeolites was studied. Laboratory assays were carried out across 4 sets of variables: different COD/SO4 2-ratios, different airflow levels, with and without natural zeolites and room and mesophilic controlled temperatures. The microaerobic process demonstrated hydrogen sulfide removal levels exceeding 90% in most cases, while maintaining the flammable condition of the generated biogas. The level of COD removal exceeded 75% in UASB reactors despite their operation under very low hydraulic retention times (2.8-4.8 hours). The effectiveness of natural zeolites in accelerating UASB reactor startup was demonstrated. Results showing the positive influence of zeolites on the granulation process in UASB reactors were also achieved.